1998
DOI: 10.1042/bj3300021
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II potentiates adrenocorticotrophic hormone-induced cAMP formation in bovine adrenal glomerulosa cells through a capacitative calcium influx

Abstract: Angiotensin II (AngII) plays a crucial role in the control of aldosterone biosynthesis in adrenal glomerulosa cells through the stimulation of two distinct Ca2+ entry pathways: (1) opening of voltage-operated calcium channels, and (2) activation of a capacitative Ca2+ entry that is dependent on calcium release from intracellular pools. Adrenocorticotrophic hormone (ACTH), on the other hand, a major hormonal regulator of steroidogenesis, induces an increase in intracellular cAMP through the activation of a G-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 44 publications
(51 reference statements)
4
39
0
Order By: Relevance
“…The marked reduction of the inhibitory action of thapsigargin in the absence of added Ca 2+ and in the presence of EGTA indicates that Ca 2+ released from intracellular stores plays only a minor role in inhibition of cyclic AMP accumulation, at most. This is consistent with the conclusion drawn from experiments on HEK 293 cells transfected with the type VI (Cooper et al, 1994) and type VIII adenylyl cyclase (Shuttleworth & Thompson, 1999), on native C6-2B glioma cells (Chiono et al, 1995;Fagan et al, 1998), on bovine adrenal glomerulosa cells (Burnay et al, 1998) and on mouse parotid acini (Watson et al, 1998) that it is Ca 2+ entry via capacitative entry channels which produces signi®cant modulation of cyclic AMP accumulation.…”
Section: Casupporting
confidence: 79%
“…The marked reduction of the inhibitory action of thapsigargin in the absence of added Ca 2+ and in the presence of EGTA indicates that Ca 2+ released from intracellular stores plays only a minor role in inhibition of cyclic AMP accumulation, at most. This is consistent with the conclusion drawn from experiments on HEK 293 cells transfected with the type VI (Cooper et al, 1994) and type VIII adenylyl cyclase (Shuttleworth & Thompson, 1999), on native C6-2B glioma cells (Chiono et al, 1995;Fagan et al, 1998), on bovine adrenal glomerulosa cells (Burnay et al, 1998) and on mouse parotid acini (Watson et al, 1998) that it is Ca 2+ entry via capacitative entry channels which produces signi®cant modulation of cyclic AMP accumulation.…”
Section: Casupporting
confidence: 79%
“…, was found in human (Cote et al, 2001), rat (Nishimoto et al, 2013) and bovine (Burnay et al, 1998) glomerulosa cells. On the contrary, a reduced cAMP formation was reported in angiotensin II -stimulated rat glomerulosa (Bell et al, 1981;Woodcock and Johnston, 1984) or bovine adrenocortical cells (Begeot et al, 1988;Marie and Jard, 1983 -inhibited isoforms (AC5 and AC6, (human: (Cote et al, 2001), rat: (Shen et al, 1997)) is a species (or cell) specific feature and may account for the different results obtained in different models.…”
Section: +mentioning
confidence: 99%
“…Although ACTH and angiotensin II act synergistically on aldosterone secretion (Spät and Hunyady, 2004), several laboratories reported that angiotensin II reduces basal and ACTHinduced cAMP production (Bell et al, 1981;Marie and Jard, 1983;Woodcock and Johnston, 1984;Begeot et al, 1987) (but see (Baukal et al, 1994;Burnay et al, 1998)). This inhibition has been attributed to the activation of the inhibitory G-protein, G i (Enyedi et al, 1986;Hausdorff et al, 1987;Lu et al, 1996;Maturana et al, 1999;Rocco et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…2A, ϩCa) (12). The transient rise in [Ca 2ϩ ] i has been attributed to the release of internal stores, while the sustained levels are a result of influx of extracellular calcium to fill these depleted membrane stores (1,4,42). The maximal [Ca 2ϩ ] i measured is referred to as peak calcium, while the sustained calcium level is reported as the calcium concentration 3-5 min after agonist treatment.…”
Section: Extracellular Calcium Is Required For Star Transcriptionmentioning
confidence: 99%